Impact of Soil Infestation of Rice Root-Knot Nematode and Flooding on its Development and Rice Yield - Dangal, NK; Sharma-Poudyal, D; Shrestha, SM; Adhikari, C (Nepal Journal of Science and Technology, 2011)
A pot experiment was conducted during July-November 2006 in a glass house at the Institute of Agriculture and Animal Science, Rampur, Chitwan to find out the impact of soil infestation of rice root-knot nematode (Meloidogyne graminicola Golden and Birchfield) and flooding on its development and rice yield. The experiment was conducted in a 4 factorial randomized complete block design with 5 replications. Rice cv. 'Sabitri' was sown in M. graminicola infested soil and infestation free (healthy) soil. Both beds were further divided to give wet bed (flooded) and dry bed condition. Twenty-one days old seedlings from each seedbed were transplanted into plastic pots containing 5 kg of M. graminicola infested and healthy soil each treated with lowland (continuously flooded) and upland condition. Simulated field conditions were created throughout the experiment period. Results revealed that rootknot index (RKI) and population of second stage juveniles of M. graminicola (J2) in soil and roots were significantly lower and grain yield was higher in pots containing seedlings transplanted from wet seedbed than dry bed. Lower RKI, root lesion index (RLI) and J2 population in soil and roots and higher grain yield were observed in pots containing seedlings transplanted from healthy seedbed than the nematode infested seedbed. Similarly, RKI, RLI and J2 population in soil and roots were significantly lower in simulated lowland as compared to upland condition. Transplanting on healthy soil also resulted in lower RKI, RLI and J2 population in soil and roots and higher grain yield than in the nematode infested soil. Interactions revealed that highest grain yield was obtained from seedlings grown under healthy seedbed transplanted in healthy soil under simulated lowland condition. Thus, M. graminicola infestation may be minimized by growing seedlings in healthy and wet seedbed. Seedling transplanting into M. graminicola free soil and lowland condition may be another important control measure for it. Key words: dry bed; lowland; upland; wet bed; rice root-knot nematode; Meloidogyne graminicola DOI: 10.3126/njst.v11i0.4086 Nepal Journal of Science and Technology 11 (2010) 31-36